Pseudohyperkalaemia. Issue 6499 (28th September 1985) - Kerr, D J; McAlpine, L G; Dagg, J H
Abstract : When the serum potassium concentration is raised and there is no clinical or electrocardiographic evidence of hyperkalaemia pseudohyperkalaemia must be considered.